Core beliefs/content accommodation policies and teaching practice. Issue 1 (3rd July 2018) - Steimel, Sarah
ABSTRACT: After nearly five years of litigation and public debate, the University of Utah now follows a Content Accommodations policy that outlines how students may ask for university curriculum to be altered based on their sincerely held beliefs. This essay is written about experiences teaching at another public university in Utah (Weber State), which has a similar Core Beliefs policy written in the aftermath of the University of Utah lawsuit. Teaching under a core beliefs policy has resulted in at least three notable influences on my own teaching practices: tensions between planning and spontaneity, vagaries surrounding reasonable accommodation, and pre-curation (or self-censorship) strategies.